Women’s knowledge, attitudes and practices related to mother-to-child transmission of HTLV-1 in Peru - Juan Macalupu; Francesca Ginocchio; Alejandra Paiva; Paloma Cusihuallpa; Diana Rodríguez-Hurtado; Fernando Mejía-Cordero; Elsa González-Lagos; Eduardo Gotuzzo (PLOS Global Public Health, 2026)
Human T-cell Lymphotropic Virus type 1 (HTLV-1) can be transmitted from mother to child through breastfeeding and increases the risk of mortality and morbidity from inflammatory, infectious and neoplastic diseases. Short-duration breastfeeding or exclusive formula feeding reduces transmission. In Peru, where breastfeeding is common and populations affected by HTLV-1 lack access to safe water and sewage, which hinders control, understanding women’s knowledge, attitudes, and practices regarding HTLV-1 mother-to-child transmission (MTCT) is essential. We conducted a descriptive, exploratory cross-sectional survey at the Instituto de Medicina Tropical Alexander von Humboldt (Lima, Peru) between September and December 2022. Women aged 18–60 years living with HTLV-1 completed a 30-item instrument (29 closed-ended, one open-ended) assessing knowledge of HTLV-1 MTCT, attitudes toward pregnancy and breastfeeding, and related practices. Descriptive statistics were calculated, and free-text responses were thematically summarized. Of 45 survey entries, 43 unique responses were analyzed (median age 45 years [IQR 38-55.5]). Most participants resided in Metropolitan Lima (77%) and had access to water and sewage services (98%), limiting generalizability to higher-burden settings in Peru. Knowledge of HTLV-1 transmission was high: sexual transmission (95%), breastfeeding (93%), and blood transfusion (86%). Among women with children (N = 40), only nine had been diagnosed prior to any pregnancy; six recalled receiving breastfeeding counseling and adhered to recommendations (five exclusive formula, one breastfeeding